2004
DOI: 10.1088/0029-5515/44/10/002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced core transport in T-10 and TEXTOR discharges at rational surfaces with low magnetic shear

Abstract: It has been observed in the T-10 tokamak that immediately after off-axis electron cyclotron resonance heating (ECRH) switch-off, the core electron temperature stays constant for some time, which can be as long as several tens of milliseconds, i.e. several energy confinement times (τ E), before it starts to decrease. Whether or not the effect is observed depends critically on the local magnetic shear in the vicinity of the q = 1 rational surface, which should be close to zero. It is hypothesized that a small sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 10 publications
(16 reference statements)
4
28
1
Order By: Relevance
“…The safety factor q characterizes a helicity of magnetic field lines, / q m n = . This result was found in experiments on many tokamaks: TCV [17], T-10 [18][19][20], and JET [21][22][23].…”
Section: Internal Transport Barriers (Itbs)supporting
confidence: 63%
“…The safety factor q characterizes a helicity of magnetic field lines, / q m n = . This result was found in experiments on many tokamaks: TCV [17], T-10 [18][19][20], and JET [21][22][23].…”
Section: Internal Transport Barriers (Itbs)supporting
confidence: 63%
“…If one fully understands the role of inverse cascade of energy associated with this process, one can exert some control of this process (such as ECCD or high-power central ECRH plus offaxis ECRH profile control) to direct the energy transition for the best effects or a steady-state barrier rather than a transient one as discussed here. Although there are several plausible mechanisms relating to the observed phenomena, such as the central low-frequency zonal flow, nonlocal transport, plasma rotation, or magnetic shear [5][6][7]18,19], the underlying physics responsible for the formations of these structures are still not clear. More detailed studies on the three-dimensional structure of the observed low-frequency mode and its nonlinear coupling with high-frequency turbulence are necessary and will be the subject of further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments have been performed on various devices to clarify the formation of the transport barrier with reduced transport triggered by localized heating and fueling, such as pellet injection, supersonic molecular beam injection (SMBI), high-Z impurity injection, and electron cyclotron resonance heating (ECRH) [1][2][3][4][5][6][7]. There are two types of explanations relating to these phenomena [5][6][7]. One is relevant to the current profile, the magnetic shear or plasma rotation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations